A PATIENT WITH DRUG REACTION WITH EOSINOPHILIA AND SYSTEMIC SYMPTOMS (DRESS) AND STEVEN-JOHNSON SYNDROME (SJS) INDUCED BY DAPSONE - Nur Annisa Nugraheningtyasari, Ari Baskoro (South Eastern European Journal of Public Health, 2025)
Severe Cutaneous Adverse Reactions (SCAR) include Drug reactions with Eosinophilia and Systemic Symptoms (DRESS) and Steven-Johnson Syndrome (SJS) which can be fatal conditions. This report discusses the case of a 24-year-old male patient who developed DRESS and SJS after taking dapsone as part of Multi-Drug Treatment (MDT) for multibasilar leprosy (MB). The patient showed early symptoms in the form of a morphiform rash and icterus, followed by complaints of fever and weakness. Although supportive therapy and systemic corticosteroids were given, the patient's condition worsened with the appearance of lesions of the oral mucosa, bulla, and positive Nikolsky signs, indicating progression to SJS. The patient eventually died from septic shock. The report emphasizes the importance of early discontinuation of causative drugs and comprehensive supportive care in the management of complex SCAR cases.